2006
DOI: 10.1080/00365520500495789
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of same day bi-directional endoscopy in the evaluation of patients with occult gastrointestinal bleeding

Abstract: A PBS was found in only 50% of the patients. Colonoscopy had a slightly higher diagnostic yield, and as expected, resulted in a significantly higher cancer detection rate than OGD. In older patients, colonoscopy should be done irrespective of the findings at OGD. Gastrointestinal-specific symptoms and the use of ASA/NSAIDs were not predictive in finding or localizing PBS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 18 publications
1
20
2
Order By: Relevance
“…These results differ significantly from the previous U.S. studies in which gastric cancer was not detected and in all cases, the rates of colon cancer far exceeded those of gastric cancer [3, 5, 14, 16]. These previous studies mirror U.S. cancer registry data where colorectal cancer surpasses that of gastric cancer [10].…”
Section: Discussioncontrasting
confidence: 91%
See 2 more Smart Citations
“…These results differ significantly from the previous U.S. studies in which gastric cancer was not detected and in all cases, the rates of colon cancer far exceeded those of gastric cancer [3, 5, 14, 16]. These previous studies mirror U.S. cancer registry data where colorectal cancer surpasses that of gastric cancer [10].…”
Section: Discussioncontrasting
confidence: 91%
“…This is higher in comparison to the previous literature with detection rates of 38% to 64% [3, 5, 8, 1416]. Our low detection rate of clinically relevant lesions may be the result of several issues.…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…10,11 Some studies showed that evaluation of the upper gastrointestinal tract helped to identify important lesions in symptomatic patients and those with iron deficiency anemia; 12,13 however, others concluded that esophagogastroduodenos copy was unjustified because important findings in the upper gastrointestinal tract were rare [14][15][16][17] and sometimes irrelevant to the results of fecal occult blood testing. [18][19][20][21] This controversy is re lated to the heterogeneity of study populations and to the limitations of the formerly used guaiac-based fecal occult blood test, [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] which was not able to distinguish bleeding in the lower gastrointestinal tract from that originating in the upper tract.…”
mentioning
confidence: 99%
“…In the case of the simulated patient with occult gastrointestinal blood loss, the frequency of endoscopic findings was based on published literature estimates of the diagnostic yield of EGD in identifying a bleeding source in patients with fecal occult blood loss [23–26]. Suitable estimates of the diagnostic yield of EGD in a cohort restricted to recent AMI and fecal occult blood could not be identified in the published literature.…”
Section: Methodsmentioning
confidence: 99%